2021
DOI: 10.1002/ejhf.2094
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myosin‐binding protein C in the diagnosis and risk stratification of acute heart failure

Abstract: Aims Cardiac myosin‐binding protein C (cMyC) seems to be even more sensitive in the quantification of cardiomyocyte injury vs. high‐sensitivity cardiac troponin, and may therefore have diagnostic and prognostic utility. Methods and results In a prospective multicentre diagnostic study, cMyC, high‐sensitivity cardiac troponin T (hs‐cTnT), and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) plasma concentrations were measured in blinded fashion in patients presenting to the emergency department with acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…In our study, MyBP-C showed positive correlations with established HF biomarkers (NT-proBNP and hs-TnI), which highlights its potential as an additional diagnostic tool in AHF, especially in cases where conventional biomarkers may not provide conclusive results. The relationship of MyBP-C with NT-proBNP and hs-TnI is supported by previous reports and is driven by the complex changes in AHF associated with cardiac injury, myocardial stretching, and cardiac pressure overload [39][40][41]. The diagnostic accuracy and prognostic value in AHF can be improved by a multimarker approach, which allows the evaluation of different pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our study, MyBP-C showed positive correlations with established HF biomarkers (NT-proBNP and hs-TnI), which highlights its potential as an additional diagnostic tool in AHF, especially in cases where conventional biomarkers may not provide conclusive results. The relationship of MyBP-C with NT-proBNP and hs-TnI is supported by previous reports and is driven by the complex changes in AHF associated with cardiac injury, myocardial stretching, and cardiac pressure overload [39][40][41]. The diagnostic accuracy and prognostic value in AHF can be improved by a multimarker approach, which allows the evaluation of different pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 73%
“…MyBP-C has been reported in many studies as a novel biomarker in myocardial infarction, which may help to quantify cardiomyocytes injury even more accurately than hs-TnI [35,36]. Also, due to its role in cardiac contraction and relaxation, dephosphorylation and subsequent release into the circulation was observed in patients with heart failure [37][38][39][40][41][42]. Furthermore, MyBP-C has emerged as a potential therapeutic target for the treatment of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…3 (4) Despite cMyC having a sarcomeric location and kinetic profile that differs from cTnT/I, its concentration is similarly increased by chronic myocardial injury and acute (non-ischaemic) myocardial injury. 3,4 Based on these results the diagnostic performance of cMyC is similar to cTnT/I. Whilst this is a remarkable accomplishment, the question remains whether cMyC has sufficient distinctive advantage to possibly replace cTnT/I or add enough incremental value to be used in conjunction with cTnT/I?…”
mentioning
confidence: 87%
“…Organ injury may be a major mechanism of the deleterious effects of congestion in patients with acute HF 6 . Kozhuharov et al 9 . studied patients presenting to the emergency department with acute dyspnoea and showed that plasma levels of cardiac myosin‐binding protein C (cMyC), a marker of myocardial injury, were higher in those with acute HF and were a marker of increased risk of all‐cause mortality [hazard ratio (HR) 2.19, 95% confidence interval (CI) 1.66‐2.89; P < 0.001 for patients above median cMyC concentrations].…”
Section: Acute Heart Failurementioning
confidence: 99%